L'éducation à la santé et la formation personnelle du futur enseignant - Olena Momot; Serhii Novik; Yevheniia Shostak; Olena Zhdanova-Nedilko (Éducation et Socialisation)
The purpose of the article is to substantiate the process of educating the health culture of a future teacher. Among the theoretical research methods, the main ones were: conceptual and comparative analysis (study of pedagogical, philosophical and psychological literature, textbooks on the research topic); structuralsystem analysis (theoretical analysis of problems, modeling of the studied systems, comparative, comparative and retrospective analyzes, diagnostics and forecasting of initial approaches and research consequences). The research model helps to improve the process of educating a future teacher's personality in terms of creating a health-preserving environment of higher education, is able apply to creatively acquired healthpreserving knowledge, skills and abilities in practice as well as to find, process, analyze, use information independently, think nonlinearly, use modern content in future teacher's activities, methods of education, technologies, pedagogical techniques, acquire the necessary personal qualities, selfchange and strive for continuous self-improvement. The education of a health culture for a future teacher’s personality is a purposeful, structures and managed system of ideas and principles, indicators, levels, criteria, guidelines and recommendations, as well as certain organizational and pedagogical conditions and tools, united by a single concept; it is aimed at individual creative development of a future specialist's personality in the structure of multilevel pedagogical education.